2022
DOI: 10.1021/acs.jafc.1c06207
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of Geographical Origins of Wolfberry (Lycium barbarum L.) Fruits Using Stable Isotopes, Earth Elements, Free Amino Acids, and Saccharides

Abstract: To develop sophisticated approaches for distinguishing goji origins, 325 wolfberry fruit samples of a certain cultivar, plant age, drying method, and collection season were gathered from 26 producing areas across Northwest China in 2017 and 2018. We employed 49 indices, including stable isotopes, earth elements, soluble amino acids, and saccharides, to identify the regions of origin of these goji fruits. Analysis of variance (ANOVA) and heritability analysis were used to assess the effects of the environment (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Citrostadienol is a compound of sterols in LB which had antioxidant property ( Chen, et al, 2019 ), whereas lyciumionoside A is a terpenoid compound isolated from LB with anti-proliferative activity ( Wang, et al, 2016 ). Recently, a series of free amino acids were used as metabolites markers to differentiate the LB of Ningxia (Zhongning city) from those originating from other provinces, suggested that amino acids played a crucial role for discriminating origins of LB ( Gong, et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…Citrostadienol is a compound of sterols in LB which had antioxidant property ( Chen, et al, 2019 ), whereas lyciumionoside A is a terpenoid compound isolated from LB with anti-proliferative activity ( Wang, et al, 2016 ). Recently, a series of free amino acids were used as metabolites markers to differentiate the LB of Ningxia (Zhongning city) from those originating from other provinces, suggested that amino acids played a crucial role for discriminating origins of LB ( Gong, et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The Lycium barbarum fruits of different tree ages were collected by researcher Ying Wang from South China Botanical Garden of the Chinese Academy of Sciences in 2017 and identi ed as the dried fruits of Lycium barbarum L. [12]. They were protected from light and moisture.…”
Section: Methodsmentioning
confidence: 99%
“…However, they cannot effectively distinguish the geographic origin of TCM due to insufficient compound information. A chemometrics strategy that combines stable isotope ratios has emerged as a promising approach for distinguishing regional origins, particularly in rice, honey, milk, and wolfberry ( Magdas et al., 2008 ; Wang et al., 2020 ; Zhao et al., 2020 ; Gong et al., 2022 ). A stoichiometric strategy incorporating stable isotope ratios has also emerged as a highly promising approach for identifying the geographic origin of various products.…”
Section: Introductionmentioning
confidence: 99%